Local and Landscape‐Level Environmental Conditions Drive Habitat Selection Across Terrestrial Mammal Species - Björn H. Franke; Aafke M. Schipper; Tal Avgar; Luca Börger; Nilanjan Chatterjee; Thomas Müller; Brian J. Smith; Briana Abrahms; Abdullahi H. Ali; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; et al. (Global Ecology and Biogeography, 2026)
Aim Animal movements are a fundamental process affecting communities and ecosystems. Quantifying habitat selection across species and habitats is key for understanding how animals respond to environmental change. Currently, we lack comparative studies that examine how habitat selection varies across species traits and landscapes. We aim to quantify global patterns of habitat selection to help understand the fundamental drivers of movement behaviour. Location Global. Time Period Contemporary. Major Taxa Studied Terrestrial mammals. Methods We estimated selection coefficients for terrain ruggedness, vegetation productivity, human population density and distance to roads of individual terrestrial mammals through step‐selection analysis of 1344 GPS tracks across 48 species. We quantified intra‐ and interspecific variation and tested whether selection coefficients were associated with species traits and habitat availability. Results We observe an overall avoidance of roads and areas of high human population density as well as rugged terrain, with a large proportion of individuals selecting for areas of intermediate NDVI. However, we also found large intraspecific variation in habitat selection and show that this variation is predicted by local and landscape‐level environmental conditions rather than species traits. Individuals in more remote areas exhibited weaker functional responses to human presence than those in more disturbed areas. Avoidance of rugged terrain is also context‐dependent, with stronger avoidance when local ruggedness is high. The only exception to the observed intraspecific variability is consistent species‐level responses to road proximity. Main Conclusions Our findings contribute to the understanding of habitat selection by terrestrial mammals, showing that selection is largely shaped by environmental conditions and that animals exhibit high plasticity in their responses. Our results also provide further evidence for the significant impact of roads on animal movement. These insights can help us to understand the potential effects of environmental change on the behaviour of mammal species around the world.

Diel patterns and migration behaviour of sympatric Atlantic salmon (Salmo salar) and brown trout (Salmo trutta) smolts during seaward migration - John Birger Ulvund; Aslak Smalås; Rita Strand; Anders Lamberg (Frontiers in Marine Science, 2025)
Migrations between different habitats to maximise fitness are well documented in many organisms, although such migrations imply a potentially great risk when moving between habitats. For anadromous salmonids, these migrations occur between the freshwater stage in their natal rivers to coastal waters during spring/summer, where they can potentially experience high mortality rates. This study investigated the riverine migration dynamics of Atlantic salmon ( Salmo salar ) and sea trout ( Salmo trutta ) smolts with a multiple camera array over three consecutive years (2021–2023). A total of 19,238 individuals were recorded, and the dynamics of schooling behaviour and diel activity patterns were examined with respect to both intra- and interspecific traits associated with migratory behaviour. The observed pattern describes the migration dynamics for sympatric natural stocks of Atlantic salmon and sea trout over a 3-year period with little-to-no interferences with natural behaviour. Results indicate a clear diel pattern in schooling behaviour, governed by the influx of natural light, with clear species-specific differences in migratory behaviour. The observed diel pattern was less dominant later in the migration period, revealing daylight length as a factor altering migratory behaviour during the smolt run. The observed changes in migration dynamics could possibly be adapted as an anti-predator behaviour during river migration, where night/dark offers protection from visual predators, whereas safety in numbers aids predator detection and avoidance during daytime.

Arthropod diversity in constructed wetlands is affected strongly by shoreline properties but only weakly by grazing - David Åhlén; Jerker Jarsjö; Mats Jonsell; Björn K. Klatt; Lea D. Schneider; John Strand; Peter A. Hambäck (Journal of Biogeography, 2024)
Aim Aquatic‐terrestrial transition zones contain features essential for many species that often benefit wetland biodiversity. Shallow flood‐zone areas and reed beds are indicative of natural wetland habitats; however, how such features affect the native arthropod biodiversity in constructed wetlands is scarcely investigated. We asked how these shoreline features, as well as wetland shoreline properties and grazing management, influence riparian arthropod diversities and habitat specializations. Location Constructed wetlands, Sweden. Taxa Araneae, Coleoptera, Diptera. Methods Taxonomic‐, phylogenetic‐ and trait diversities, along with habitat specialist species richness, were measured in riparian spiders, beetles and selected Diptera in 68 constructed wetlands in two regions of Sweden. We ran structural equation models to estimate direct and indirect effects from shoreline slope, flooded grassland, reed areas and grazing management on group diversities, and used multivariate models to determine drivers on habitat specialist species richness. Results Flooded grassland and reed area, along with shoreline slope influenced arthropod diversities, and responses differed between arthropod groups and diversity metrics. Spider trait diversity was greater in wetlands with larger flooded grassland areas, whilst beetle trait diversity was reduced. Spider phylogenetic diversity was greater in wetlands containing larger reed areas and in wetlands with steeper shorelines. However, species richness in predatory flies was greater in wetlands with more gentle shorelines. Grazing management had limited effects on arthropod diversities; however, species richness in wetland specialist and generalist predatory dipterans was greater in the absence of grazers in wetlands with greater flooded grassland areas. Main Conclusions As requirements vary considerably among arthropods, care must be taken when constructing and managing wetlands to benefit arthropod biodiversity. The present results suggest wetlands with a varied shoreline, albeit with greater proportions of flood areas, or multiple adjacent wetlands with varying shores in a wet landscape and a mild grazing regiment, would accommodate a more diverse arthropod fauna.

Integrative demographic modelling reduces uncertainty in estimated rates of species' historical range shifts - Antonio R. Castilla; Alissa Brown; Sean Hoban; Everett Andrew Abhainn; John D. Robinson; Jeanne Romero‐Severson; Adam B. Smith; Allan E. Strand; John R. Tipton; Andria Dawson (Journal of Biogeography, 2024)
Aim Biogeographers have used three primary data types to examine shifts in tree ranges in response to past climate change: fossil pollen, genetic data and contemporary occurrences. Although recent efforts have explored formal integration of these types of data, we have limited understanding of how integration affects estimates of range shift rates and their uncertainty. We compared estimates of biotic velocity (i.e. rate of species' range shifts) using each data type independently to estimates obtained using integrated models. Location Eastern North America. Taxon Fraxinus pennsylvanica Marshall (green ash). Methods Using fossil pollen, genomic data and modern occurrence data, we estimated biotic velocities directly from 24 species distribution models (SDMs) and 200 pollen surfaces created with a novel Bayesian spatio‐temporal model. We compared biotic velocity from these analyses to estimates based on coupled demographic‐coalescent simulations and Approximate Bayesian Computation that combined fossil pollen and SDMs with population genomic data collected across the F. pennsylvanica range. Results Patterns and magnitude of biotic velocity over time varied by the method used to estimate past range dynamics. Estimates based on fossil pollen yielded the highest rates of range movement. Overall, integrating genetic data with other data types in our simulation‐based framework reduced apparent uncertainty in biotic velocity estimates and resulted in greater similarity in estimates between SDM‐ and pollen‐integrated analyses. Main Conclusions By reducing uncertainty in our assessments of range shifts, integration of data types improves our understanding of the past distribution of species. Based on these results, we propose further steps to reach the integration of these three lines of biogeographical evidence into a unified analytical framework.

Latitudinally distinct stocks of Atlantic cod face fundamentally different biophysical challenges under on‐going climate change - Olav Sigurd Kjesbu; Maud Alix; Anne Britt Sandø; Espen Strand; Peter J. Wright; David G. Johns; Anders Thorsen; C. Tara Marshall; Kjell Gunnar Bakkeplass; Frode B. Vikebø; Mari Skuggedal Myksvoll; Geir Ottersen; et al. (Fish and Fisheries, 2023)
The reproductive success of marine ectotherms is especially vulnerable in warming oceans due to alterations in adult physiology, as well as embryonic and larval survival prospects. These vital responses may, however, differ considerably across the species' geographical distribution. Here we investigated the life history, focusing on reproductive ecology, of three spatially distant populations (stocks) of Atlantic cod ( Gadus morhua , Gadidae) (50–80° N), in the Irish/Celtic Seas‐English Channel Complex, North and Barents Seas, under past and projected climate. First, experimental tracking of spawning behaviour evidenced that the ovulation cycle is highly distressed at ≥9.6 (±0.25)°C ( T up ). This knife‐edge threshold resulted in erratic spawning frequencies, whereas vitellogenin sequestration remained unaffected, indicating endocrine rather than aerobic scope constraints. Cod in the Celtic Sea‐English Channel are, therefore, expected to show critical stock depensation over the next decades as spawning grounds warm above T up , with Irish Sea cod subsequently at risk. Second, in the relatively cooler North Sea, the northward retraction of Calanus finmarchicus (Calanidae) and Para‐Pseudocalanus spp. (Clausocalanidae) (1958–2017) limit cod larvae feeding opportunities, particularly in the southernmost subarea. However, the contrasting increase in Calanus helgolandicus (Calanidae) does not counteract this negative effect, likely because cod larvae hatch ahead of its abundance peaks. Overfishing again comes as a twin effect. Third, in the still relatively cold Barents Sea, the sustainably harvested cod benefit from improved food conditions in the recent ice‐free polar region but at the energetic cost of lengthier and faster spawning migrations. Consequently, under climate change local stocks are stressed by different mechanistic factors of varying management severity.

Evaluating expert‐based habitat suitability information of terrestrial mammals with GPS‐ tracking data - Maarten J. E. Broekman; Jelle P. Hilbers; Mark A. J. Huijbregts; Thomas Mueller; Abdullahi H. Ali; Henrik Andrén; Jeanne Altmann; Malin Aronsson; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; Jerrold L. Belant; et al. (Global Ecology and Biogeography, 2022)
Aim Macroecological studies that require habitat suitability data for many species often derive this information from expert opinion. However, expert‐based information is inherently subjective and thus prone to errors. The increasing availability of GPS tracking data offers opportunities to evaluate and supplement expert‐based information with detailed empirical evidence. Here, we compared expert‐based habitat suitability information from the International Union for Conservation of Nature (IUCN) with habitat suitability information derived from GPS‐tracking data of 1,498 individuals from 49 mammal species. Location Worldwide. Time period 1998–2021. Major taxa studied Forty‐nine terrestrial mammal species. Methods Using GPS data, we estimated two measures of habitat suitability for each individual animal: proportional habitat use (proportion of GPS locations within a habitat type), and selection ratio (habitat use relative to its availability). For each individual we then evaluated whether the GPS‐based habitat suitability measures were in agreement with the IUCN data. To that end, we calculated the probability that the ranking of empirical habitat suitability measures was in agreement with IUCN's classification into suitable, marginal and unsuitable habitat types. Results IUCN habitat suitability data were in accordance with the GPS data (> 95% probability of agreement) for 33 out of 49 species based on proportional habitat use estimates and for 25 out of 49 species based on selection ratios. In addition, 37 and 34 species had a > 50% probability of agreement based on proportional habitat use and selection ratios, respectively. Main conclusions We show how GPS‐tracking data can be used to evaluate IUCN habitat suitability data. Our findings indicate that for the majority of species included in this study, it is appropriate to use IUCN habitat suitability data in macroecological studies. Furthermore, we show that GPS‐tracking data can be used to identify and prioritize species and habitat types for re‐evaluation of IUCN habitat suitability data.

Body size and digestive system shape resource selection by ungulates: A cross‐taxa test of the forage maturation hypothesis - Saeideh Esmaeili; Brett R. Jesmer; Shannon E. Albeke; Ellen O. Aikens; Kathryn A. Schoenecker; Sarah R. B. King; Briana Abrahms; Bayarbaatar Buuveibaatar; Jeffrey L. Beck; Randall B. Boone; Francesca Cagnacci; Simon Chamaillé‐Jammes; et al. (Ecology Letters, 2021)
The forage maturation hypothesis (FMH) states that energy intake for ungulates is maximised when forage biomass is at intermediate levels. Nevertheless, metabolic allometry and different digestive systems suggest that resource selection should vary across ungulate species. By combining GPS relocations with remotely sensed data on forage characteristics and surface water, we quantified the effect of body size and digestive system in determining movements of 30 populations of hindgut fermenters (equids) and ruminants across biomes. Selection for intermediate forage biomass was negatively related to body size, regardless of digestive system. Selection for proximity to surface water was stronger for equids relative to ruminants, regardless of body size. To be more generalisable, we suggest that the FMH explicitly incorporate contingencies in body size and digestive system, with small‐bodied ruminants selecting more strongly for potential energy intake, and hindgut fermenters selecting more strongly for surface water.

Diversity, divergence and density: How habitat and hybrid zone dynamics maintain a genomic cline in an intertidal barnacle - John P. Wares; Allan E. Strand; Erik E. Sotka (Journal of Biogeography, 2021)
Aim As within‐species genomic data have been shown useful in interpreting broader biogeographic trends, we analysed the mode of population genomic isolation involved in a well‐studied intertidal genomic cline to better understand the mechanisms maintaining it. These results were interpreted in the context of spatial variation in habitat use and availability as well as likely fitness consequences for hybridization between the two lineages. Location Pacific coast of North America. Taxon Arthropods (Class Maxillopoda, Order Sessilia, Family Balanidae; Balanus glandula ). Methods Genotype‐by‐sequencing approaches were used to generate single‐nucleotide polymorphism markers across sites sampled between southern Alaska and Southern California. Inference using standard population genomic methods, including analysis of population structure, inbreeding and linkage disequilibrium, was used to identify the steepest transitions across the largest number of loci examined. These data were put in the context of observed population density and habitat availability. Results We show that the majority of markers analysed show strong clinal transitions in a very narrow portion of the California coast. Patterns of linkage disequilibrium among markers, along with prior evidence of variation in reproductive potential by latitude and by mitochondrial lineage, suggest some reproductive isolation among the northern and southern lineages of B. glandula that are concordant with the drop in population density and habitat availability in central California. Main Conclusions A significant clinal transition in genomic diversity is stronger and more localized than previously recognized and exhibits statistical patterns suggesting that the lineages are reproductively and phenotypically distinct in ways that may be ecologically important. As this species has been used to infer process in coastal biogeography, further study of concordant patterns will be important for advancing our understanding of this region.

Global stakeholder vision for ecosystem‐based marine aquaculture expansion from coastal to offshore areas - Ibon Galparsoro; Arantza Murillas; Kemal Pinarbasi; Ana M.M. Sequeira; Vanessa Stelzenmüller; Ángel Borja; Anne Marie O´Hagan; Adele Boyd; Suzanne Bricker; Joxe Mikel Garmendia; Antje Gimpel; Aline Gangnery; et al. (Reviews in Aquaculture, 2020)
Marine aquaculture is the most promising industry for ensuring future provision of seafood. Yet, the worldwide growth and expansion of this industry have been slower than expected, calling for the identification of environmentally suitable sites while accounting for all factors that could constrain or benefit its establishment. Here, we determine the main obstacles and risks hindering the growth and expansion of marine aquaculture, as well as the needs and recommendations to overcome such constraints. Our analysis is based on results obtained from a consultation process held in 16 study sites located around the world with the participation of 614 stakeholders representing the research community, aquaculture industry, government, conservation groups, and education and fishermen associations. A high level of commonality exists in the main issues hindering aquaculture growth and expansion in coastal, off‐the‐coast and offshore aquaculture with most being attributed to interactions with other maritime activities, including conflicts with other users and administrative procedures, including licensing. Critical needs for improved management and expansion of the aquaculture industry are related to planning and management of developments and technological advances, with economic and market needs featuring to a lesser extent. Key procedures recommended to assist further aquaculture growth are the standardisation and simplification of regulatory frameworks, improvement of governance, and the adoption of participatory processes to facilitate meaningful and productive stakeholder engagement. We strongly recommend stakeholder participation to enhance insights on the full environmental and human dimensions of marine management and for implementation of ecosystem‐based marine spatial planning.

Forecasting the genetic influences of red drum stock enhancement in South Carolina - Christopher J. Katalinas; John D. Robinson; Allan E. Strand; Tanya Darden; Karl Brenkert; Michael R. Denson (Fisheries Management and Ecology, 2019)
The South Carolina Department of Natural Resources ( SCDNR ) began stocking red drum, Sciaenops ocellatus (Linnaeus), in 1989 to augment the abundance of juveniles available for recreational harvest in South Carolina estuaries. While stock enhancement can help supplement wild populations under high fishing pressure, releasing hatchery‐raised fish into the wild also presents the risk of decreased genetic diversity. An individual‐based model ( IBM ) was developed to forecast the genetic influences of stocking on the wild spawning population to inform responsible stocking strategies. Model results indicated the SCDNR red drum stock enhancement programme should maintain mean contributions of stocked fish no greater than 30% per year class over a 45‐year stocking period, coupled with at least 10 effective breeders in the hatchery replaced annually, to maintain current levels of genetic diversity estimated in the wild population. The IBM is a useful tool for hatchery managers to guide responsible stock enhancement.

A global database of nitrogen and phosphorus excretion rates of aquatic animals - Michael J. Vanni; Peter B. McIntyre; Dennis Allen; Diane L. Arnott; Jonathan P. Benstead; David J. Berg; Åge Brabrand; Sébastien Brosse; Paul A. Bukaveckas; Adriano Caliman; Krista A. Capps; Luciana S. Carneiro; et al. (Ecology, 2017)
Animals can be important in modulating ecosystem‐level nutrient cycling, although their importance varies greatly among species and ecosystems. Nutrient cycling rates of individual animals represent valuable data for testing the predictions of important frameworks such as the Metabolic Theory of Ecology ( MTE ) and ecological stoichiometry ( ES ). They also represent an important set of functional traits that may reflect both environmental and phylogenetic influences. Over the past two decades, studies of animal‐mediated nutrient cycling have increased dramatically, especially in aquatic ecosystems. Here we present a global compilation of aquatic animal nutrient excretion rates. The dataset includes 10,534 observations from freshwater and marine animals of N and/or P excretion rates. These observations represent 491 species, including most aquatic phyla. Coverage varies greatly among phyla and other taxonomic levels. The dataset includes information on animal body size, ambient temperature, taxonomic affiliations, and animal body N:P. This data set was used to test predictions of MTE and ES , as described in Vanni and McIntyre (2016; Ecology DOI : 10.1002/ecy.1582 ).

Erratum: Late glacial and holocene 10 Be production rates for western Norway - Brent M. Goehring; Øystein Strand Lohne; Jan Mangerud; John Inge Svendsen; Richard Gyllencreutz; Joerg Schaefer; Robert Finkel (Journal of Quaternary Science, 2012)

Late glacial and holocene 10 Be production rates for western Norway - Brent M. Goehring; Øystein Strand Lohne; Jan Mangerud; John Inge Svendsen; Richard Gyllencreutz; Joerg Schaefer; Robert Finkel (Journal of Quaternary Science, 2012)
We present a new regional calibration of the 10 Be production rate from two well‐dated surfaces in southern Norway: a rock avalanche with 14 C‐dated wood and a precisely dated Younger Dryas moraine. Calculated 10 Be production rates are 4.26 ± 0.13 and 4.65 ± 0.14 at g −1 a −1 for the Lal/Stone and Lifton scaling models, respectively. Our regional production rate for southern Norway is 5% lower than the canonical global 10 Be production rate with lower uncertainties. Our 10 Be production rate agrees with regional 10 Be production rates from north‐eastern North America and New Zealand. The 10 Be production rate estimate presented here can be used to improve the precision and accuracy of exposure‐dated ice‐marginal features, as well as other surfaces, in northern Europe. Copyright © 2011 John Wiley & Sons, Ltd.

Underwater Optical Imaging: Status and Prospects - Julles Jaffe; Karl Moore; John McLean; Michael Strand (Oceanography, 2001)

Anaerobic transformation of 1,1,1-trichloroethane by municipal digester sludge - Chun Chen; Bhasker S. Ballapragada; Jaakko A. Puhakka; Stuart E. Strand; John F. Ferguson (Biodegradation, 1999)

The development of submerged macrophytes in Lake Ringsjön after biomanipulation - John A. Strand (Hydrobiologia, 1999)

Minireview: Biomanipulation as an Application of Food-Chain Theory: Constraints, Synthesis, and Recommendations for Temperate Lakes - Lars-Anders Hansson; Helene Annadotter; Eva Bergman; Stellan F. Hamrin; Erik Jeppesen; Timo Kairesalo; Eira Luokkanen; Per-Åke Nilsson; Martin Søndergaard; John Strand (Ecosystems, 1998)

Mechanisms regulating abundance of submerged vegetation in shallow eutrophic lakes - S. E. B. Weisner; John A. Strand; Håkan Sandsten (Oecologia, 1997)

Effect of light internsity on vesicle formation in Chlorobium - Margrethe Broch-Due; John G. Ormerod; Bente Strand Fjerdingen (Archives of Microbiology, 1978)